Destination management: theoretical background and present practice - Becková, Helena; Nováková, Božena (Melandrium, 2016)
Destination management is an advanced form of tourism management successfully applied abroad where it develops constantly. Destination management came into focus there as early as the sixties of the 20th century, while in the Czech Republic quite a bit later, approximately in the second half of the nineties. This is apparent also in professional literature. An array of authors, both foreign and domestic, engage in destination management at present. However, the domestic authors proceed primarily from foreign experience as destination management hasn't a long tradition in the Czech Republic. Destination management is based on cooperation of involved subjects, which is regarded as an important prerequisite for further development of tourism. Nevertheless, cooperation of various subjects from the public and the private sector isn't an easy matter and so attention is aimed to various approaches to effective destination management. The paper deals with theoretical background of destination management. Besides, an item of interest is also its application in practice. The paper examines principally the situation in the Czech Republic with the aim to find out the level of tourism management in its particular destinations.
Destinační management: teoretická východiska a současná praxe
Keywords: destination management; tourism; destination management organizations; destinační management; cestovní ruch; organizace destinačního managementu